Property Utilization in Creating Creative Dance - Nelli, Destri; Hayati, Suci; Frimals, Aeron; Septi, Sabila Eka; Putri, Fhadira Insani (Jurnal Pedagogi dan Pembelajaran, 2023)
Dance properties play an important role in helping dancers to move freely. The nature of dance needs to be developed and known by students in learning because it is very important as in learning the art of dance. The purpose of this study was to compare the utilization of tariff property with two indicators, namely messaging support and add artistic value at the elementary school level. This research method uses quantitative research with a sampling technique that is total sampling with a population of 68 students in four elementary schools. Types of Instruments in this study using a type of questionnaire instrument. Data analysis techniques used in this study are descriptive statistical tests and inferential tests in the form of assumptions and hypothesis tests. Based on the results of the study it can be seen that there are significant differences and comparisons in the utilization of tariff properties on the messaging support and add artistic value indicators in the four schools at the elementary school level. lack of dance properties in the school. So it is necessary to equalize property in various schools to increase the beauty of the dance performed by students. The implication of this research is knowing the importance of utilizing dance properties will have an impact on adding aesthetic value to dance students at the elementary school level.